Molar Volume and Viscosities of Hydroxylamine Hydrochloride in Methanol-Water (50:50 v/v) at 303.15 K - Shrivastava, Shilpi; Dixit, Ajita (Asian Journal of Chemistry, 2011)
Densities and viscosities of hydroxylamine hydrochloride (NH3OH·Cl) were measured as a function of their concentration in methanol-water (50:50 v/v) at 303.15 K. This data is used to determine value of apparent molar volume (φv), limiting apparent molar volume (φ* v), experimental slope (S* v), molar volume (V) and excess molar volume (VE). The viscosity of electrolyte systems in mixed solvent was also studied. Viscosity data was used to determine B-coefficient (B) and constant characteristic of ion-ion interactions (A), excess viscosity (ηE) and excess molar free energy of activation of flow (GE). The interaction parameter Gurenberg and Nissan (d) was also calculated and reported. The parameter are analyzed to evaluated to understand solute-solvent interaction.